Integrating Collective Efficacy and Criminal Opportunity: Disorder, the Built Environment, and Policing - Lanfear, Charles Christian (My University, 2021)
This dissertation proposes an integrative theory that links social structural explanations of neighborhood crime to opportunity-based situational explanations for crime. The first chapter of this dissertation argues that the neighborhood-level theories of collective efficacy and broken windows may be unified into a multilevel theory of situations using Cohen and Felson’s (1979) routine activities theory and a pragmatist model of roles and perception. I discuss empirical implications of this integrated theory. The second chapter proposes that collective efficacy inhibits crime in part by permitting neighborhoods to remove and prevent built environment features that generate criminal opportunities. I find evidence collective efficacy is negatively related to the presence of abandoned buildings and mixed land use which, in turn, promote crime. The third chapter interrogates the role of police efficacy---resident perceptions of police effectiveness and legitimacy---in collective efficacy theory. In contrary to established research in this area, I find evidence that collective efficacy causally precedes police efficacy. In the conclusion I discuss implications for future research and advocate for situating collective efficacy in a multi-level crime, opportunity, and political economy framework.
Thesis (Ph.D.)--University of Washington, 2021
Keywords: built environment; collective efficacy; policing; routine activities; social control; Sociology; Criminology; Sociology